Determining the elements of TVET teachers competency for Nigerian Higher Learning Institutions - Chee, Sern Lai; Hamisu, Mohamad; Mohd Salleh, Kahirol (IOP Publishing, 2018)
This paper determined the suitable elements of competency framework to be applied for Nigerian higher learning institutions. Lack of competent TVET teachers in Nigerian higher institutions has led to several problems such as low quality graduates and unemployment. Competency is a vital element for assessing the quality of technical and vocational education and training (TVET) teachers. Therefore, this research determined the suitable elements of competency model to be applied to Nigerian TVET higher institutions based on Malaysian Human Resource Development Practitioners (MHRDP) competency model for workplace learning and performance (WLP). The study was fully quantitative and 218 cross sectional survey instrument was systematically distributed to TVET teachers from five higher institutions and 205 questionnaires were retrieved based on the stratified sampling technique. Exploratory factor analysis (EFA) was conducted to analyse the data. The research discovered that there are 19 elements relevant to the competency framework for TVET teacher Nigerian TVET higher institutions. A similar research should be undertaken to extend the result to reflect other Non-TVET institutions in Nigeria.